ANALISIS STRATEGI BAURAN PEMASARAN TERHADAP VOLUME PENJUALAN BATIK INDRAGIRI DI KABUPATEN INDRAGIRI HULU - Gustiani, Andina; Jahrizal, Jahrizal; Heri, Helwen (Jurnal Tepak Manajemen Bisnis, 2018)
This study aims to analyze the influence of product, price, promotionand place influence on sales Indragiri Batik In Indragiri Hulu. The studypopulation is consumers who buy batik as much as 529 consumers. The samplesize that will be used is 121 people. Data used in this research are primary dataand secondary data. Methods of data collection using questionnaires. The dataanalysis used is descriptive and quantitative. Data analysis used in this researchis multiple linear regression analysis. The results of this study affect productIndragiri Batik Sales Volume in Indragiri Hulu district. For that quality productssuch as batik materials, motifs and colors would be very important for the buyers.The better the product then the sales volume will increase. Price effect onIndragiri Batik Sales Volume in Indragiri Hulu district. For that price set shouldbe a concern, by providing affordable prices and discounts on each purchase witha certain amount, of course when compared with competitor products willincrease sales volume. The more affordable the set price then the sales volumewill increase. Promotion affects Indragiri Batik Sales Volume in Indragiri Huludistrict. For that promotion made batik craftsmen especially personal sales andget a bonus on every purchase is very important. Place influences to IndragiriBatik Sales Volume in Indragiri Hulu district. This indicates that the place candetermine the sales volume. For that batik selling place is very important for thebuyer or consumer batik easy to reach and easy access menunju menokasi is veryimportant.